Agritourism and Peer-to-Peer Accommodation: A Moderated Mediation Model - Ibrahim A. Elshaer; Alaa M. S. Azazz; Faleh A. Ameen; Sameh Fayyad (Agriculture, 2022)
Agritourism is not a new phenomenon; moreover, it has increased significantly over the past decade and is expected to continue growing in the future. Despite this growth, there is no shared understanding of agritourism, which is problematic because it creates confusion and diminishes its appeal among consumers, thereby impeding communication and collaboration between stakeholders. Agritourism activities can be carried out on a microscale in rural areas by families and agricultural practitioners or on a large scale by hotels, restaurants, and catering firms. Despite many developing countries’ agricultural potential, agritourism has not been inserted into development plans in these countries. Only agritourism in small accommodation enterprises is carried out on a microscale by rural families. This study seeks to test the relationship between the positive impacts of peer-to-peer (P2P) accommodation and agritourism performance, with the mediating effects of support for P2P accommodations and organizational citizenship behavior towards P2P accommodations. The data were derived from 300 Airbnb consumers and hosts of agritourism accommodations in the eastern province of the kingdom of Saudi Arabia (KSA). The results of “Structural Equation Modeling” (SEM) via the “Partial least squares” (PLS) showed a positive direct relationship between peer-to-peer accommodation and agritourism performance with a significant mediating role of Organizational Citizenship Behavior and a positive moderating role of information on Agritourism destinations. Several theoretical and practical implications are discussed.